2017
DOI: 10.1371/journal.pone.0172936
|View full text |Cite
|
Sign up to set email alerts
|

SP-LL-37, human antimicrobial peptide, enhances disease resistance in transgenic rice

Abstract: Human LL-37 is a multifunctional antimicrobial peptide of cathelicidin family. It has been shown in recent studies that it can serve as a host’s defense against influenza A virus. We now demonstrate in this study how signal peptide LL-37 (SP-LL-37) can be used in rice resistance against bacterial leaf blight and blast. We synthesized LL-37 peptide and subcloned in a recombinant pPZP vector with pGD1 as promoter. SP-LL-37 was introduced into rice plants by Agrobacterium mediated transformation. Stable expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Japonica cv. Dongjinbyeo), and as a result transgenic plants exhibited enhanced resistance against various plant pathogenic organisms. However, expression of LL‐37 in transgenic plants for molecular farming and subsequent analysis of the heterologous product have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Japonica cv. Dongjinbyeo), and as a result transgenic plants exhibited enhanced resistance against various plant pathogenic organisms. However, expression of LL‐37 in transgenic plants for molecular farming and subsequent analysis of the heterologous product have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Human cathelicidin LL-37 has been used widely for developing many transgenic crops in the past few years (Jung, 2013;Jung et al, 2012;Lee et al, 2017). It was found that LL-37 is susceptible to salt toxicity resulting from deactivation in highly alkaline medium.…”
Section: Discussionmentioning
confidence: 99%
“…Although slight variations in plant–microbe composition in root and leaf microbiota have been reported in previous studies on tobacco plants (Weinhold, Dorcheh, Li, Rameshkumar, & Baldwin, ), existing plant pathogens have already developed a high resistance to the endogenous AMPs of plants. In surveys of other types of peptides, the microbial peptides of animal origin are found to be less toxic, highly efficient and quicker in inhibiting pathogens (Lee et al, ). Therefore, integrating animal‐origin exogenous AMPs into plant genomes presents an excellent way to protect plants without affecting their natural plant microbial composition and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind the application of antimicrobial peptides and proteins, genetically modified (GM) plants can be the platform of choice for their expression. Research shows that it is possible to successfully express a wide variety of antimicrobial proteins in plants, starting from those which can protect crops against bacteria (Lee et al 2017), but also those which can be subsequently used as biopharmaceuticals with or without a later purification step (Paškevičius et al 2017;Company et al 2014). Recombinant protein production in edible plants or those used as an animal feed gives a possibility of cutting the costs of product extraction and purification.…”
Section: Introductionmentioning
confidence: 99%